Dental anxiety level of children patient during dental treatment using CFSS-DS questionnaire - Yuwannisa, Mutiara; Runkat, Jakobus; Indriyanti, Ratna (Padjadjaran Journal of Dentistry, 2013)
The anxiety during dental treatment is an obstacle for both adult and children patients. The aim of this study was to describe data of the dental anxiety experienced by 6 - 9 year old patients grouped by their age and gender. The type of this study was descriptive observational and the samples were collected using incidental sampling method. The total number of sample were 63 patients who came to Dental Hospital of Faculty of Dentistry Universitas Padjadjaran Bandung during August 2011. This research was using the CFSS-DS questionnaire to measure the patient’s anxiety. This research was conducted by interviewing the patients about how they feel during the dental treatment. The result of this study showed that the 7-years-old boy patients seem to have higher anxiety levels than the 6-years-old, or younger ones. Meanwhile, in 6-years-old and younger girl patients showed higher anxiety level than the older (7, 8, and 9-year-old) ones. The anxiety level of children patients during dental treatment were different based on their age and gender.